2014
DOI: 10.3389/fncom.2014.00130
|View full text |Cite
|
Sign up to set email alerts
|

Liquid computing on and off the edge of chaos with a striatal microcircuit

Abstract: In reinforcement learning theories of the basal ganglia, there is a need for the expected rewards corresponding to relevant environmental states to be maintained and modified during the learning process. However, the representation of these states that allows them to be associated with reward expectations remains unclear. Previous studies have tended to rely on pre-defined partitioning of states encoded by disjunct neuronal groups or sparse topological drives. A more likely scenario is that striatal neurons ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These percentage connectivity values worked the best in terms of accuracy, for the neuron parameter selections in this work shown in Table 2. The strengths of all the connections (W[0,1]NPRE×NPOST) were selected randomly (Maass et al, 2002) from a uniform distribution U (0, 1) (Toledo-Suárez et al, 2014; Srinivasan et al, 2018). A randomly generated mask (M{0,1}NPRE×NPOST,mijM) decides which connections exist to obtain the desired sparsity/percentage connectivity (PPREPOST=msub(i,j)mij(NPRE×NPOST)×100%).…”
Section: Methodsmentioning
confidence: 99%
“…These percentage connectivity values worked the best in terms of accuracy, for the neuron parameter selections in this work shown in Table 2. The strengths of all the connections (W[0,1]NPRE×NPOST) were selected randomly (Maass et al, 2002) from a uniform distribution U (0, 1) (Toledo-Suárez et al, 2014; Srinivasan et al, 2018). A randomly generated mask (M{0,1}NPRE×NPOST,mijM) decides which connections exist to obtain the desired sparsity/percentage connectivity (PPREPOST=msub(i,j)mij(NPRE×NPOST)×100%).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not obvious how the environmental states are represented in the reinforcement learning of the basal ganglia. Based on the hypothesis that the striatum responds to diverse inputs from different cortical sources and plays a computational role for discriminating inputs in reinforcement learning-based decision making, the LSM properties of a striatal microcircuit were studied with computational models (Toledo-Suárez et al, 2014). It was demonstrated that the separation and approximation properties required for the LSM are generated using a model network of medium spiny neurons and fast spiking interneurons coupled via inhibitory synapses in a supervised learning task.…”
Section: Brain Regionsmentioning
confidence: 99%